Marketing Margin of White Bawal Fish (Pampus Argenteus) on CV. Alam Mulia Bahari, Panipahan Village, Pasir Limau Kapas District, Rokan Hilir Regency, Riau Province - Rosdiana Tarigan; Eni Yulinda; Hazmi Arief (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research was conducted in March 2018, located in PanipahanVillage, Pasir Limau Kapas District, Rokan Hilir Regency, Riau Province, to find out the marketing channels of white pomfret (Pampus Argenteus) at CV. Alam Mulia Bahari, Panipahan Village. Analyze the costs, profits and margins of pomfret marketing white (Pampus Argenteus) in CV. Alam Mulia Bahari, Panipahan Village. The method used in this research is survey method, namely by observing directly. The number of fishermen as many as fishermen, the owner of CV. Alam Mulia Bahari 3 people, employees of CV. Alam Mulia Bahari 10 people and the method of taking respondents is by census. Whereas the sampling of traders is by sampling, consisting of 5 egents, 10 retailers, 5 along-along merchants.The result showed that there were two marketing channels at CV. Alam Mulai Bahari, Panipahan Village, Pasir Limau Kapas Village, Rokan Hilir Regency, Riau Province. In the marketing channels I, the total marketing costs was IDR. 2,300/kg, total marketing profit of IDR.2,700/kg and marketing margin of IDR.5,000 per kg. For marketing channels II the total marketing cost is IDR. 3,000 per kg, the total marketing profit IDR. 4,000 per kg, and the Subdistrict, Rokan Hilir Regency, Riau Province. Then the marketing channel I is the most efficient marketing channel for White Bawal Fish with a low marketing margin of IDR. 5,000 and has high marketing value 0f 87.5% Kata Kunci: Margin, Costs, Benefits, Marketing Channels